SISTEM UNDI DALAM BUDAYA DEMOKRASI: Mencari Pemimpin Gereja Dengan Perspektif Jabatan Sebagai Pemberian TUHAN. - Gerhard Sipayung (Institut Agama Kristen Negeri Toraja, 2021)
This study aims to make the lottery system a solution in the selection of spiritual/ephorus leaders to avoid conflicts of interest and horizontal in the leadership period. The facts that the democratic culture of choosing synod leaders, often makes pastors and congregation members trapped in following patterns such as regional head elections and presidential elections. The impact that occurs is divisions in the church, the formation of groups, seizures and demands for positions as compensation from the elected leader of the successful team that won the leader, a black campaign that maybe true and maybe slanderous before and after the election This, of course, makes the congregation anxious and the loss of function as a servant, the level of trust of the congregation to the leader decreases. If this is allowed, then there is no difference between the church and secularism, the philosophy of the church as the salt of the earth is no longer relevant. This study uses a qualitative approach with library methods and facts in the field. The results of the study show that; first, the leader who is elected by the lottery system must first have the ethical and spiritual standards as a spiritual leader's competence. Second, the lottery system prevents the elected leader from being responsible only to certain groups. Third, the lottery system forms leaders who are elected to uphold biblical values ​​as social control within and outside the church. Penelitian ini bertujuan agar sistem undi menjadi solusi dalam pemilihan pemimpin rohani/ephorus untuk menghindari konflik kepentingan dan horizontal dalam masa kepemimpinan. Fakta di lapangan, budaya demokrasi memilih pemimpin sinode, sering membuat para pendeta dan anggota jemaat terjebak mengikuti pola seperti pemilihan kepala daerah dan pemilihan presiden. Dampak yang terjadi adalah perpecahan dalam gereja, terbentuk kelompok-kelompok, perebutan dan tuntutan jabatan sebagai balas jasa dari pemimpin yang terpilih dari tim sukses yang memenangkan pemimpin tersebut, kampanye hitam yang mungkin saja benar dan bisa saja fitnah pra dan pasca pemilihan. Hal ini tentu membuat keresahan jemaat dan hilangnya fungsi jabatan sebagai pelayan, tingkat kepercayaan jemaat kepada pemimpin berkurang. Jika ini dibiarkan, maka tidak ada perbedaan antara gereja dengan sekularisme, filosofi gereja sebagai garam dunia tidak relevan lagi. Penelitian ini menggunakan pendekatan kualitatif dengan metode pustaka serta fakta di lapangan. Hasil dari penelitian menunjukkan bahwa; pertama, pemimpin yang terpilih dengan sistem undi harus terlebih dahulu memenuhi standar etika dan rohani sebagai kompetensi pemimpin rohani. Kedua, sistem undi menghindarkan pemimpin yang terpilih bertanggungjwawab hanya kepada kelompok tertentu. Ketiga, sistem undi membentuk pemimpin yang terpilih menegakkan nilai-nilai Alkitab sebagai kontrol sosial ke dalam maupun ke luar gereja.